In situ XAFS Study of Palladium Electrodeposition at the Liquid/Liquid Interface. (1st May 2017) - Booth, Samuel G.; Chang, Sin-Yuen; Uehara, Akihiro; La Fontaine, Camille; Cibin, Giannantonio; Schroeder, Sven L.M.; Dryfe, Robert A.W.
Abstract: We report the use of XAFS (X-ray absorption fine structure) as an in situ method to follow the electrochemically driven deposition of palladium nanoparticles at a liquid/liquid interface. A novel glass/plastic hybrid electrochemical cell was used to enable control of the potential applied to the liquid/liquid interface. In situ measurements indicate that the nucleation of metallic nanoparticles can be triggered through chronoamperometry or cyclic voltammetry. In contrast to spontaneous nucleation at the liquid/liquid interface, whereby fluctuations in Pd oxidation state and concentration are observed, under a fixed interfacial potential the growth process occurs at a steady rate leading to a build-up of palladium at the interface. Raman spectroscopy of the deposit suggests that the organic electrolyte binds directly to the surface of the deposited nanoparticles. It was found that the introduction of citric acid results in the formation of spherical nanoparticles at the interface.